Experimental Investigation of Low Reynolds Number Flow Around a Serrated NACA 0015 Airfoil - Hassan, Mohamed Ibren; Andan, Amelda Dianne; Asrar, Waqar; Aldheeb, Mohammed; Saad, Mohd Rashdan (Semarak Ilmu, 2023)
The study of low Reynolds number flows has triggered the interest of many researchers. This concern is attributed to the presence of various vortex structures that significantly affect aerodynamic performance. The study of such phenomena offers an opportunity to better understand and predict the behavior of fluid flows in three dimensions, leading to improved design strategies for aerodynamic systems. This study intends to examine the performance of different NACA 0015 airfoil configurations namely, baseline, serration, comb, comb-serration and poro-serrated, emphasizing on their influence on aerodynamic characteristics and flow structure. Experimental work is performed to provide valuable insights into the behavior of the flow field and the underlying physical phenomena. The current study has shown that the mean streamwise velocity of the serrated, combed, and comb-serrated configurations exhibit more stable flow patterns compared to the baseline airfoil. These patterns suggest a promising approach for delaying flow separation. In contrast, the poro-serrated model exhibited a more disordered flow pattern. Remarkably, when subjected to a 10-degree angle of attack, all the modified trailing-edge designs showcased minimal separation zones compared to the baseline configuration. At the same angle, the baseline's shear layer disintegrates, while the poro-serrated model displays increasing disturbance and separation. Conversely, the comb-serrated and serration models exhibit a smaller increase in unsteadiness. Furthermore, the study indicated that Musou black paint exhibits a higher rate of light absorption compared to flat black paint, but it demonstrates higher reflection levels on a poro-serrated surface. Collectively, the outcomes of this investigation hold significant implications for enhancing aerodynamic system designs.